Four-top quark physics at the LHC - Freya Blekman; Fréderic Déliot; Valentina Dutta; Emanuele Usai (Universe, 2022)
The production of four top quarks presents a rare process in the Standard Model that provides unique opportunities and sensitivity to Standard Model observables including potential enhancement of many popular new physics extensions. This article summarises the latest experimental measurements of the four-top quark production cross section at the LHC. An overview is provided detailing interpretations of the experimental results regarding the top quark Yukawa coupling in addition to the limits on physics beyond the Standard Model. Further, prospects for future measurements and opportunities offered by this challenging final state are given herein.